Analisis Tingkat Minat Siswa dan Faktor-Faktor yang Mempengaruhinya dalam Mengikuti Ekstrakurikuler Olahraga di Madrasah Aliyah Se-Desa Montong Gamang - Muhammad Salabi; Intan Kusumawardani; Irna Ningsi Amalia Rachman (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to analyze the level of student interest and the influencing internal and external factors in participating in sports extracurricular activities at Madrasah Aliyah in Montong Gamang Village. The research was motivated by the low student participation observed in extracurricular sports, both in terms of attendance and active engagement. A descriptive quantitative approach was employed using a survey method. A total of 90 students were selected from a population of 450 through proportional random sampling. The data collection instrument was a four-point Likert scale questionnaire comprising two main dimensions: internal factors (interest, attention, and activity) and external factors (environment and parental support). The results showed that the average student interest score was 98.71 with a standard deviation of 8.53, with most students categorized as having low (42.2%) or high (41.1%) levels of interest. The mean score for internal factors was 63.12 (SD = 7.42), and for external factors, 35.21 (SD = 6.34). These findings indicate the need for improvement through strategies that enhance intrinsic motivation, foster supportive learning environments, and increase parental involvement. This study provides a novel contribution to the development of sports extracurricular programs in rural-based madrasah settings, which have been underrepresented in the physical education literature.